The Relationship of Dental Pulp Stone with Cardiovascular and Renal Disease: A Cross Sectional Study: Dental Pulp Stone with Cardiovascular and Renal Disease - Zulfiqar, Roma; Qazi, Fazal Ur Rehman; Ram, Gobind; Kumar, Aroon; Jabbar, Ayesha Abdul; Tanveer, Maham; Jat, Shahbaz Ahmad (Pakistan Journal of Health Sciences, 2025)
Calcification of bodily tissues can occur by pathological or physiological means due to deposition of calcium. Normally, calcium deposits in teeth and bone, but ectopic areas in the body such as kidneys, vascular system and joints may precipitate calcium due to imbalance in the metabolism of calcium results hypercalcemia is known as metastatic calcification. Objective: To determine the association of pulp stones with cardiovascular and renal disease. Methods: Through non-probability sampling, cross-sectional study was carried out over the course of six months at the Department of Operative Dentistry and Endodontics, DUHS, Karachi. The current study comprised 150 patients, both male and female, between the ages of 30 and 60, who had teeth with pulp stones; individuals without pulp stones were not included. The chi-square test was utilized to evaluate the relationship between dental pulp stones and the existence of cardiovascular and renal disorders, and SPSS was used for data analysis. Results: Females were mostly affected as compare to males (63%).The mean age of the patients was noted as 42.2 years.A significant association between dental pulp stones cardiovascular and renal disease was documented. (p=0.001). Conclusion: A significant association was observed between CVD and pulp stones (p-value 0.001) and also significant association was established between PS and RS (p-value 0.001).